2021
DOI: 10.1093/jphsr/rmab060
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to decrease COVID-19 vaccine hesitancy for children

Abstract: Objectives This study aims to understand acceptable strategies to enhance the COVID-19 vaccine uptake among mothers who have no intention to vaccinate their children. Methods In a cross-sectional study, using an online survey in March 2021, we evaluated the variables within the Health Belief Model (severity, susceptibility, benefits, barriers and cues to action) along with parents’ sociodemographic characteristics, previous C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
4
5
0
Order By: Relevance
“…Our findings contribute to an emerging literature suggesting that there is a low demand for childhood COVID-19 vaccine among parents ( 7 9 , 11 , 17 ). A study conducted in Texas, USA reported that about 38.3% of mothers had no intention to consider COVID-19 vaccine for their children ( 17 ).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our findings contribute to an emerging literature suggesting that there is a low demand for childhood COVID-19 vaccine among parents ( 7 9 , 11 , 17 ). A study conducted in Texas, USA reported that about 38.3% of mothers had no intention to consider COVID-19 vaccine for their children ( 17 ).…”
Section: Discussionsupporting
confidence: 70%
“…Our findings contribute to an emerging literature suggesting that there is a low demand for childhood COVID-19 vaccine among parents ( 7 9 , 11 , 17 ). A study conducted in Texas, USA reported that about 38.3% of mothers had no intention to consider COVID-19 vaccine for their children ( 17 ). The proportion of willing parents in India is considerably lower as compared to other countries as per studies from England (89%) ( 7 ); New Zealand (80%) ( 18 ); China (73%) ( 19 ); USA (65%) ( 20 ); Canada (63%) ( 10 ); Japan (42.9%) ( 15 ) and Turkey (42%) ( 21 ).…”
Section: Discussionsupporting
confidence: 70%
“…Our findings contribute to an emerging literature suggesting that there is a low demand for childhood COVID-19 vaccine among parents(79,11,16). A study conducted in Texas, USA reported that about 38.3% of mothers had no intention to consider COVID-19 vaccine for their children(16).…”
Section: Discussionsupporting
confidence: 70%
“…Our findings contribute to an emerging literature suggesting that there is a low demand for childhood COVID-19 vaccine among parents(79,11,16). A study conducted in Texas, USA reported that about 38.3% of mothers had no intention to consider COVID-19 vaccine for their children(16). Proportion of willing parents in India is considerably lower as compared to other countries as per studies from England (89%)(7); New Zealand (80%)(17); China (73%)(18); USA (65%)(19); Canada (63%)(10); and Turkey (42%)(20).…”
Section: Discussionsupporting
confidence: 70%
“…The COVID-19 vaccine is worrying for some parents who have not vaccinated their children, and this concern stems from three main sources: (1) the lack of severe symptoms of COVID-19 in children [28] , [29] , [30] ; (2) the adverse events after vaccination, such as fatigue, dizziness, injection pain and even myocarditis [31] , [32] , [33] , [34] , [35] , [36] ; (3) insufficient clinical data on the efficacy of each vaccine [37] . In fact, this hesitancy of parents is unnecessary, because more than 65% of the side effects caused by the COVID-19 vaccine in children is relieved or ceases within 1–3 days [38] , [39] , [40] , [41] . Furthermore, clinical data proves that vaccines authorized for children have significantly shown strong efficacy in preventing infection and reducing the risk of morbidity of COVID-19 in children [42] , [43] , [44] , [45] , [46] , [47] , [48] .…”
Section: Introductionmentioning
confidence: 99%